Task-Based Representation of Moving Images - Goodrum, Abby (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
What role does task play in the representation of visual information? Does the nature of the task at hand drive the need for either visual or textual representations for moving images? This paper is a report of research conducted to construct a task-based framework for the representation of moving images. This study measured the degree of congruence between moving images and their representations, both text and image based, in a non-retrieval environment with and without task constraints.